The efficiency of chronic disease care in sub-Saharan Africa - Geldsetzer, Pascal; Ortblad, Katrina; Bärnighausen, Till (BMC medicine, 2016)
The number of people needing chronic disease care is projected to increase in sub-Saharan Africa as a result of expanding human immunodeficiency virus (HIV) treatment coverage, rising life expectancies, and lifestyle changes. Using nationally representative data of healthcare facilities, Di Giorgio et al. found that many HIV clinics in Kenya, Uganda, and Zambia appear to have considerable untapped capacity to provide care for additional patients. These findings highlight the potential for increasing the efficiency of clinical processes for chronic disease care at the facility level. Important questions for future research are how estimates of comparative technical efficiency across facilities change, when they are adjusted for quality of care and the composition of patients by care complexity. Looking ahead, substantial research investment will be needed to ensure that we do not forgo the opportunity to learn how efficiency changes, as chronic care is becoming increasingly differentiated by patient type and integrated across diseases and health systems functions.Please see related article: http://bmcmedicine.biomedcentral.com/articles/10.1186/s12916-016-0653-z.
Gesehen am 28.05.2020